2012
DOI: 10.1111/j.1365-2621.2012.03122.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification and characterisation of angiotensin I‐converting enzyme–inhibitory peptides derived from catfish (Clarias batrachus) muscle protein thermolysin hydrolysates

Abstract: Summary The angiotensin I‐converting enzyme (ACE)‐inhibitory activities of catfish (Clarias batrachus) muscle protein hydrolysates were investigated. Thermolytic digests of C. batrachus sarcoplasmic and myofibrillar proteins exhibited inhibitory activity towards ACE and were purified with the aim of ultrafiltration, gel filtration and reversed‐phase high‐performance liquid chromatography (RP‐HPLC). The amino acid sequences of hydrolysates with the highest ACE‐inhibitory activities were determined using electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
2
8
0
1
Order By: Relevance
“…Sample with molecular weight of 3 -10kDa and sample with molecular weight 10 kDa does not have any significant difference (P 0.05) and this may indicate that peptides with larger molecular weight are present in the 3 -10 kDa sample fraction. Similar findings are reported by Ghassem et al [24] whereby sample with molecular weight less than 3 kDa has the highest ACE inhibitory activity and [27] where sample with molecular weight less than 1 kDa has the highest ACE inhibitory activity. Campos et al [27] reported that the ACE inhibitory activity is affected by the peptide chain containing less than 6 hydrophobic amino acids and this is supported by Zhang et al [17] that reported the ACE inhibitory activity is affected by the presence of hydrophobic amino asid at the C-terminal of a tripeptide.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Sample with molecular weight of 3 -10kDa and sample with molecular weight 10 kDa does not have any significant difference (P 0.05) and this may indicate that peptides with larger molecular weight are present in the 3 -10 kDa sample fraction. Similar findings are reported by Ghassem et al [24] whereby sample with molecular weight less than 3 kDa has the highest ACE inhibitory activity and [27] where sample with molecular weight less than 1 kDa has the highest ACE inhibitory activity. Campos et al [27] reported that the ACE inhibitory activity is affected by the peptide chain containing less than 6 hydrophobic amino acids and this is supported by Zhang et al [17] that reported the ACE inhibitory activity is affected by the presence of hydrophobic amino asid at the C-terminal of a tripeptide.…”
Section: Resultssupporting
confidence: 89%
“…These amino acids are able to convert the molybdate in folin-phenol reagent into the blue molybdium [21,22]. According to [23][24][25][26], ACE inhibitory activity is affected by the presence of the amino acid proline, phenylalanine or tyrosin at the terminal-C of peptide chain. Therefore the increase of the soluble protein content, may increase presence of these amino acids which can affect the ACE inhibitory activity.in the ultrafiltrated sample fraction hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory kinetics of HB-IV and PeptACE on ACE were determined according to the method of Ghassem et al [ 39 ]. The ACE-inhibition were measured by varying the concentration of HHL (0.5, 1, 2, 4, and 6 mM) in the absence and presence of various concentrations of HB-IV and PeptACE.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of enzyme for the preparation of protein hydrolysate will be critical as the properties of hydrolysates will depend on the nature of enzyme. Application of different proteolytic enzymes such as alcalase, neutrase, pepsin, papain, a-chymotrypsin, trypsin, protamex and thermolysin for the preparation of protein hydrolysate from tilapia protein, tuna frame protein, Acetes chinensis and cat fish muscle protein has been achieved (Cao et al, 2010;Lee et al, 2010;Ghassem et al, 2012;Charoenphun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%